Optimalisasi Layanan Pengaduan Virtual melalui SP4N LAPOR Di Kabupaten Sidoarjo - Ramadhanti, Rizqa; Lestari, Yuni (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The government has a breakthrough in providing innovation, namely E-Government. One form of implementing E-Government is E-Service. E-service is included in the Government to Citizen (G2C). One of the implementations of E-Service in the field of public services managed by the Sidoarjo District Communication and information agency is SP4N LAPOR. SP4N LAPOR is an electronic based public complaints channel in Sidoarjo. This research method is descriptive qualitative with data collection in the form of observations, interviews and documentation. This can be related to the theory of the Public Service Complaint Management System Mechanism according to Permenpan RB No. 62 tahun 2018. The aim of this research is to optimize SP4N LAPOR as a virtual complaint service in Sidoarjo Regency. The Conclusion from this study is that the SP4N LAPOR service in Sidoarjo has been running optimally, but there are still inhibiting factors such as OPD admin mutations without knowledge and confirmation, lack of understanding of the public regarding correct complaint reports, lack of understanding regarding customer satisfaction. Suggestions that can be given are holding routine meetings between SP4N LAPOR admin besides holding outreach to the community regarding the understanding of SP4N LAPOR.   Keywords: Service, SP4N LAPOR, E-government